Influence of dendronization on spectral diffusion and aggregation in conjugated polymers - Lupton, John M.; Schouwink, Peter; Keivanidis, Panagiotis E.; Grimsdale, Andrew C.; Müllen, Klaus (My University, 2003)
Dendronization has previously been suggested as a means of controlling the level of intermolecular interactions in macromolecular and polymeric compounds. We therefore studied the spectral relaxation dynamics of dendronized and non-dendronized polyfluorenes at different temperatures. Dendronization strongly affects inhomogeneous spectral broadening, resulting in a blue-shift and broadening of the otherwise narrow vibronic progression of polyfluorene at low temperature. Using gated spectroscopy we are able to identify emissive keto defects on isolated chains of both dendronized and non-dendronized polymers, along with a strong aggregation band in the solid state. Surprisingly, the emission from chemical and structural defects is found to be stronger in the case of the dendronized material. The observation of aggregate emission in dendronized polyfluorenes suggests that aggregation in these materials does not occur through linear π-stacking, but rather through electronic interactions at point contacts between chains introduced by structural kinks along the backbone.
Keywords: Electroluminescence; Polyfluorenes; Dendrimers; Aggregation; Excitons